GEOGRAPHICAL AND CHRONOLOGICAL CLASSIFICATION OF THE EMERGENCE OF RELIGIONS - Son of Karimov Nasibjon Ikromiddin; Tursunboev Alisher (American Journals Publishing, 2024)
Religion is a maslak, a view doctrine that directly surrounds Nature, Society, man and his mind, purpose and destiny from living, expresses faith and faith in the divine power, which is beyond the environment, creates man, at the same time suddenly shows him the path of life "true", "true" and "righteous" and learns. The role of religion in the life of society as a spiritual and spiritual value is multifaceted in its function. Man is different from other creatures in his spiritual essence. To do this, humanity must look at the human principles of religious doctrine, which are the mainstay of spirituality. Religion has long been a holistic system of ideas and views, which, as a component of human spirituality, embodies the high ideals of humanity, dreams of truth and truth, dishonesty and justice, strengthening them in the form of stable rules. Religion will never lead mankind to a bad path. Religion reminds us that this world is fleeting, that the afterlife, that a person encourages his child to be vigilant, to walk away from dirty roads, to be good, to leave a good mark.
Keywords: Religion, Spirituality, classification of religions, animism, fetishism, totemism, shamanism, witchcraft.